Characterization of the Conus bullatus genome and its venom-duct transcriptome - Hu, Hao; Bandyopadhyay, Pradip K; Olivera, Baldomero M; Yandell, Mark (BMC genomics, 2011)
Background The venomous marine gastropods, cone snails (genus Conus ), inject prey with a lethal cocktail of conopeptides, small cysteine-rich peptides, each with a high affinity for its molecular target, generally an ion channel, receptor or transporter. Over the last decade, conopeptides have proven indispensable reagents for the study of vertebrate neurotransmission. Conus bullatus belongs to a clade of Conus species called Textilia , whose pharmacology is still poorly characterized. Thus the genomics analyses presented here provide the first step toward a better understanding the enigmatic Textilia clade. Results We have carried out a sequencing survey of the Conus bullatus genome and venom-duct transcriptome. We find that conopeptides are highly expressed within the venom-duct, and describe an in silico pipeline for their discovery and characterization using RNA-seq data. We have also carried out low-coverage shotgun sequencing of the genome, and have used these data to determine its size, genome-wide base composition, simple repeat, and mobile element densities. Conclusions Our results provide the first global view of venom-duct transcription in any cone snail. A notable feature of Conus bullatus venoms is the breadth of A-superfamily peptides expressed in the venom duct, which are unprecedented in their structural diversity. We also find SNP rates within conopeptides are higher compared to the remainder of C. bullatus transcriptome, consistent with the hypothesis that conopeptides are under diversifying selection.